Economic growth, defence expenditure and threats in Nigeria 1980-2013: Bound co-integration analysis - Umar, Muhammed Aminu; Abu Bakar, Abu Sufian (Medwell Journals, 2015)
The research of Benoit (1973, 1978) has triggered a great deal of research interest on the defense expenditure and growth relationship, however, the findings still remain inconclusive.The variations are attributed largely to the distinctive socioeconomic factors associated with different countries; availability of data, methodological differences, models and diverse econometric techniques employed.Furthermore, studies conducted on this aspect in Nigerian context, concentrate in examining the causal relationship between economic growth and defence expenditure.Recently, the activities of deadly “Boko Haram” and Niger Delta Militant have threatened the country.This research aims at testing the impacts of defense expenditure and threats on economic growth in Nigeria, between 1980 and 2013 on the basis of Aizeman and Glick arguing that defense expenditure in the presence of threats can stimulate economic growth. The study adopts the robust ARDL Model to solve most of the problems associated with Cointegration analysis in the presence of small sample size and mix integration order.The ARDL results revealed that there is significant long run relationship between defence expenditure and threat on economic growth in Nigeria both in the short and long run conditions.The result further indicates bidirectional positive relationship between defence expenditure and economic growth in Nigeria while threat has unidirectional negative impact running from threat to economic growth.One of the policy implication of the study is that the policy makers should revisit the funding of defence sector as the current 0.5% budget is seen as grossly inadequate for the defence sector while considering the internal threats and the global military expenditure trend.